The Optimization of Double Pan Design for Household Use Based on Weight Reduction Using Taguchi Method - Novia Intan Maharani; Wahyu Ardiansyah; Ira Setyaningsih (Journal of Industrial Engineering and Halal Industries, 2025)
Abstract. Double pans are widely used in household kitchens due to their convenience and cooking efficiency. However, many users report discomfort caused by the excessive weight, particularly when flipping the pan during cooking. This study aimed to optimize the double pan design by focusing on reducing its weight using the Taguchi method. Three controllable factors were selected: pan material, handle material, and shaft material. An L9 orthogonal array was employed to efficiently design the experiments. The measured responses included total pan weight score assessed through the CAD simulation. Signal-to-noise ratio analysis was also conducted to identify the most influential factors and determine the optimal design combination. The findings indicate that material significantly affect user comfort, while pan weight is primarily influenced by material choice. This study demonstrates the applicability of the Taguchi method in consumer product design and provides a reference for developing lightweight and user-friendly kitchenware.